C-111 Progress toward poliomyelitis eradication—Nigeria, January 2014 to July 2015. (January 2016) - Etsano, Andrew; Gunnala, Rajni; Shuaib, Faisal; Damisa, Eunice; Mkanda, Pascal; Ticha, Johnson; Banda, Richard; Korir, Charles; Chevez, Ana; Enemaku, Ogu; Corkum, Melissa; Davis, Lora; et al.
Abstract : Since the 1988 launch of global polio eradication efforts, 4 of the 6 World Health Organization regions have been certified polio-free. In the remaining regions (African & Eastern Mediterranean), only Nigeria, Afghanistan, and Pakistan have never interrupted wild poliovirus (WPV) transmission. During 2003 to 2013, Nigeria was a reservoir for WPV reintroduction into 26 previously polio-free countries. In 2012 a national emergency plan was launched to intensify polio eradication efforts in Nigeria. This report summarizes Nigeria's polio status during January 2014 to July 2015. During this period, 13 polio vaccination campaigns were implemented. No WPV cases have been reported in 2015 (versus 6 during the same 2014 period). Onset of the last reported WPV type 1 case was July 24, 2014 in Kano. One case of circulating vaccine-derived poliovirus type 2 (cVDPV2) has been reported in 2015, compared with 30 cases reported in 2014. With 12.8 non-polio acute flaccid paralysis cases per 100, 000 nationally, polio surveillance exceeds the international standard of ≥2 but subnational gaps remain. Of 8 WPV genetic clusters detected in Nigeria in 2012, 4 persisted in 2013 and 2 in 2014. Environmental surveillance at 38 sites identified no WPV and one cVDPV2 positive sample in 2015 linked to a 2005 emergent strain from Nigeria. Pending laboratory testing of specimens collected through July 23, Africa is poised to be certified polio-free as early as 2017. This will require maintaining political support and program funding in the absence of WPV transmission, ensuring high levels of population immunity, including in children in the security compromised northeast, and strengthening surveillance in poor-reporting districts.